Development of lung fluke, Paragonimus heterotremus, in rat and mice, and the role of paratenic host in its life cycle - Doanh, Pham Ngoc; Hien, Hoang Van; An, Pham Thanh; Tu, Luu Anh (Academia Journal of Biology, 2015)
Lung fluke, Paragonimus heterotremus, has been identified as the important pathogen for human paragonimiasis in Vietnam. Eating under cooked mountain crabs, which are contaminated with P. heterotremus metacercariae, is confirmed as the route of infection. In this study, we identified the role of paratenic host in the life cycle of P. heterotremus by experimental infection to house rat (Rattus tanizumi) and mice BALB/c, and then transferred to cats. The results showed that P. heterotremus metacercariae developed to adults in the lungs of rats. In contrast, they remain as juvenile worms in liver and muscles of mice. These juveniles developed to adults when they were transferred to cats, confirming that mice serve as the role of paratenic hosts in the life cycle of P. heterotremus in Vietnam. Thus, investigation for natural paratenic hosts of P. heterotremus is necessary, and not eating uncooked/undercooked meat of other animals in addition to mountain crabs should be added to prevention of paragonimus infection. Development of different size metacercariae of P. heterotremus in rats and mice were also discussed herein.